Accounting Conservatism in the COVID-19 Period: Evidence from Indonesia’s Conventional Commercial Banks - Atik - Isniawati; Rahmawati - Rahmawati; Ari Kuncara Widagdo; Agung Nur Probohudono; Jombrik - Jombrik (Postgraduate Program Merdeka University, 2024)
This study assesses the level of accounting conservatism in terms of the timeliness of loan loss provisions (LLP). We use a sample of Indonesia's conventional commercial banks over 2018Q1â€“2021Q4. The total sample was 1270 observations over 16 quarters. This study focuses on the impact of the implementation of credit restructuring policies during the COVID-19 pandemic on accounting conservatism in terms of the timeliness of LLP. Our findings of conventional commercial banks are not conservative, meaning that there is a delay in recognition of LLP, as evidenced by the positive and significant influence of Î”NPLt-1 and Î”NPLt on LLP. However, the effect of Î”NPLt+1 on LLP is negative and significant. This result is thought to have happened because, in 2018, banks had begun to change their behaviour towards counter-cycles in accordance with PSAK71. However, the change was disrupted due to the issuance of credit restructuring policies during the COVID-19 pandemic. This study is expected to provide information regarding the effects of credit restructuring policies during the COVID-19 pandemic on banks' conservative behavior.DOI: https://doi.org/10.26905/afr.v7i1.12254Â